Drivers of Pigeon Pea Consumption Among School-Aged Children in Central Tanzania - Gichohi-Wainaina, Wanjiku N.; Mremi, Ruth; Chande, Monica; Msuya, John M.; Kumwenda, Nelson C.; Muzanila, Yasinta C.; Msere, Harry; Muhimbula, Happiness; Bekunda, Mateete; Okori, Patrick (Frontiers in Sustainable Food Systems, 2022)
Background: Protein energy malnutrition (PEM) and iron deficiencies (ID) are of major public health concern in Tanzania including among school-aged children. PEM and ID in early childhood have serious, long-term consequences because they impede motor, sensory, social and emotional development, growth retardation, poor cognitive development, learning disability of children, lowered resistance to infectious diseases, and reduced physical work capacity. The objective of this study was to elucidate the drivers of pigeon pea consumption among school-aged children in Dodoma district, Central Tanzania. Understanding these drivers would be useful in promoting pigeon pea consumption among school-aged children as one of the strategies to increase dietary protein and iron intake. Methods: This study was a cross-sectional study in which data were collected using a questionnaire based on a combination of the Theory of Planned Behavior and Health Belief Model. The data were collected from caregivers (n = 138) in four villages in Kongwa district, Dodoma region, Central Tanzania. We used correlations and multiple regressions to assess associations between constructs and identify predictive constructs. Mann–Whitney U tests were used for score comparisons with a significant p-value set at <0.10. Results: Health value was significantly correlated with health behavior identity (rs = 0.63, p < 0.001) and also significantly predicted health behavior identity (rs = 0.49, p = 0.001). The constructs cues to action and control belief were significantly associated with intention (β = −0.41, p = 0.059 and β = 0.06, p = 0.019 respectively). Finally, we observed that intention was a significant predictor of behavior (β = 1.38, p = 0.001). We also observed a significant negative interaction between perceived barriers and intention to consume pigeon pea (β = −0.04, p = 0.006), indicating that perceived barriers limit intention to consume pigeon pea. Conclusion and Implication: Our findings indicate that when the caregiver places increased importance on preventing her school-aged child from being iron or protein deficient or indeed anemic (health value), it results in a positive evaluation of the effectiveness of giving pigeon pea to address these nutrient deficiencies. Programs and efforts aimed at promoting pigeon pea consumption should focus on educating caregivers on iron and protein deficiency and the role that pigeon pea could play in addressing these. However, perceived barriers such as pest infestation during storage need to be addressed to increase pigeon pea consumption. The involvement of post-harvest management specialists is therefore crucial. Along with this, increasing productivity and crop management is also crucial to ensure year-round affordable supply of pigeon pea.